IMPLEMENTASI METODE SIMULASI DALAM PEMBELAJARAN BERBASIS PROYEK DI KELAS VI SDN 40 MATARAM - Ramadhan Abdul Jalil; Nurfitriah, Nurfitriah; Wangi, Putri Azila; Jannah, Raudatul; Nurhaliza, Nurhaliza; Damayanti, Ni Luh Tri Dewi; Pujiyantari, Ni Ketut Satialini; Istiningsih, Siti; Putri, Hikmah Ramdhani (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the implementation of the simulation method in project-based learning (PjBL) in the sixth grade of SDN 40 Mataram. A qualitative approach with a case study method was employed. Data were collected through observations, in-depth interviews with teachers and students, and documentation of classroom activities. The results indicate that the simulation method enhances student engagement, strengthens conceptual understanding, and fosters collaboration in project work. The teacher plays a vital role as a facilitator in designing simulation scenarios that align with the project themes. Challenges encountered include limited time and supporting facilities; however, these can be addressed through careful planning and optimal use of available resources. The study concludes that the simulation method is effective in supporting the success of project-based learning at the elementary level, particularly in improving 21st-century skills such as critical thinking, communication, collaboration, and creativity.